Characteristics and adsorption mechanism of ion-exchange resin for biodiesel production / \c Muhamad Syahir Abdul Latiff - Muhamad Syahir Abdul Latiff (School of Bioprocess Engineering, University Malaysia Perlis, 2012)
Biodiesel is produced via transesterification process that involved reaction of triglycerides which is the major fatty acid content in crude palm oil (raw materials) with methanol and producing Fatty acid Methyl Ester (FAME) and glycerol. The objectives of this study is to determine and optimize process variables for the biodiesel using Response Surface Method based on central Composite Design (RSM:CCD) . The recomended optimization condition is temperature at 63.43 c, stirring speed at approximately 772.83rpm, reaction time around 120 minutes and molar ratio of methanol : oil at 13:1. Under this operating condition, the model was predicted to get 90.17% conversion of biodiesel.